Workers' self-organisation under military rule: challenges and opportunities in post-coup Myanmar - Campbell, Stephen (2024)
In February 2021, the Myanmar military seized power in a coup, bringing to an end a decade of quasi-civilian electoral rule, during which workers in Myanmar had organised themselves into close to 3000 workplace unions. The coup and post-coup imposition of martial law thus upended what had been a vigorous domestic labour movement. Yet post-coup restrictions on worker mobilising have not extinguished workers’ collective struggles. We therefore investigate, in this article, the challenges and opportunities for workers’ self-organisation under post-coup conditions. We argue that despite heightened restrictions since the coup, industrial workers have exploited contradictions in the post-coup factory labour regime to press demands and make tangible, if limited, gains. To substantiate our argument, we present two cases of worker organising at garment factories on Yangon’s industrial outskirts. Empirically, we draw on interviews we conducted with workers involved in the two cases in question, and on our ongoing research into Myanmar’s post-coup labour conditions more generally.